B2B Digital Marketing and ROI Measurement: Challenges and Opportunities in the Business-to-Business Industry for MSMEs in Indonesia - Mardiani, Eri; Utami, Eva Yuniarti; Farooq Mujahid, Muhammad Umer (West Science Interdisciplinary Studies, 2023)
In order to maintain growth and competitiveness in the modern business environment, digital marketing must be strategically integrated, especially for Micro, Small, and Medium-Sized Enterprises (MSMEs) that conduct business-to-business (B2B) transactions. This study looks into the potential and difficulties that come with B2B digital marketing as well as how to measure return on investment (ROI) for MSMEs in Indonesia. Surveys and in-depth interviews were used in a mixed-methods approach to collect both quantitative and qualitative data. The results show that MSMEs have widely adopted digital marketing tactics, with social media and content marketing being the most popular. There are still issues like tight budgets, hard ROI calculations, and fierce market competition. The report makes actionable suggestions, such as group marketing campaigns, the creation of uniform ROI measurements, and a focus on innovation via emerging technologies and niche targeting. The insights provide practitioners, policymakers, and industry stakeholders with practical advice for improving the knowledge of the dynamics in B2B digital marketing for MSMEs in Indonesia.